Robust Automatic Transfer Switch System for Managing Power Transitions between Grid, Solar PV, and Genset Sources - Syafii Syafii; Ilham Perdana Putra (Andalasian International Journal of Applied Science, Engineering, and Technology)
This article presents the design and implementation of an Automatic Transfer Switch (ATS) system with automatic generator activation, aimed at ensuring the continuity of electricity supply from the National Electricity Company (PLN) grid, photovoltaic (PV) systems, and generator sets (Gensets). As reliance on the PLN grid is often compromised by various disruptions, including short circuits and natural disasters, integrating reliable backup energy sources is essential for maintaining operational efficiency across critical sectors such as healthcare, education, and industry. The ATS is structured to facilitate seamless transitions between power sources, minimizing downtime and enhancing system reliability. Test results demonstrate the ATS's effectiveness in managing switching processes, showing minimal voltage fluctuations and flicker durations, which underscores its capability to sustain uninterrupted power supply. By employing advanced monitoring technologies, this ATS system not only optimizes energy management but also bolsters the resilience of electrical infrastructure, addressing the growing need for dependable electricity in an increasingly variable energy landscape.